TWO-DIMENSIONAL PHYSICAL MODELLING IN THE ESTUARIES OF AUR RIVER - Achmad Syarifudin; Yulinatini Eka Putri; Lindawati Lindawati; Henggar Risa Destania (STMIK Widya Cipta Dharma, 2020)
Musi River is the main river with a river length of more than 750 km and the average width of 540 m which is still affected by the tides of seawater from the thirteen existing river basin systems. Aur River is one of a tributary of the Musi River located in the Seberang Hulu area of ​Palembang city. Aur River needs to do research related to the rise in water level in the river body if extreme rainfall occurs that will cause inundation in the upstream area of ​​the river. The study was conducted with a hydraulic model approach that is using a physical model of the channel with a scale model and data from existing prototypes and with the existing conditions and the running time of the model carried out for 1.50 hours with a certain period of time data collection is carried out both erosion and sedimentation data and later obtained patterns and the total amount of bed load at the estuary of river. The results of river erosion and sedimentation patterns later. The result of the research was sediment transport patterns with three times period are 30 minutes, 60 minutes and 90 minutes so that the formed of erosion and sedimentation pattern with the total bed load be range 0.66 cubic meter per day from formula, 6.34 cubic meter per day from Einstein’s & Lane and 7.48 cubic meter per day from MPM formula.